Understanding shifts in estuarine fish communities following disturbances using an ensemble modeling framework - Dakota M. Lewis; Kevin A. Thompson; Tim C. MacDonald; Geoffrey S. Cook (Ecological Indicators, 2021)
Ecological disturbances may result in mortality events that alter biotic communities and ecosystems. In many coastal zones disturbances are increasing, including algal blooms and fish kills. These two disturbances are often related, with blooms releasing toxins or depleting oxygen, ultimately killing fish. Depending on the intensity, duration, and geographic extent of an algal bloom, the fish community can take days to years to recover from disturbances. To explore the relationship among environmental disturbances, sport fish, and forage fish communities, this study examines a non-toxic brown algal bloom (Aureoumbra lagunensis) occurring from December 2015 through March 2016. Using an ensemble modelling framework combining generalized linear models (GLM), Bayesian modelling, and Bayesian structural equation modeling (SEM), this complementary framework helped elucidate complex relationships among environmental variables and the fish community following a disturbance. The algal bloom crashed over a three-day period in March 2016 and resulted in a fish kill when dissolved oxygen concentrations dropped below hypoxic levels (DO < 2 mg/L). The bloom and subsequent fish kill led to shifts in both forage and sport fish communities, and their relationships, when compared to non-disturbed years. Both sport fish and forage fish abundances decreased following the bloom, but the response of the forage fish community was more rapid. When looking at direct correlations between individual sport fish and forage fish community metrics during the bloom, a large amount of variation in sport fish abundance was explained by forage fish abundance (R2 = 0.34). Also, the variation in forage fish abundance was explained well by pH (R2 = 0.72). Forage fish community dynamics were more closely related to water quality metrics than sport fish communities during non-disturbed periods. However, during this algal bloom, sport fish community dynamics were more closely associated with water quality metrics than forage fish community dynamics. Furthermore, sport fish community dynamics were strongly related to bloom dynamics during the three months prior to the fish kill. In the three months following the kill, the forage and sport fish communities were less strongly linked than in non-disturbed years. These large shifts in community dynamics and relationships following a disturbance suggest both forage and sport fish communities, food webs, and trophic dynamics may be at increasing risk of crossing ecological thresholds as algal blooms become more common in coastal ecosystems.